Assessment Of Quality and Utilization of PMIS in Project Success: A case study of Integrated community Based Initiatives in Kabale District, Uganda - Prudence, Kansiime (Kabale University, 2020)
This study aimed at examining project management information system on project success. The research study was done at ICOBI which has established its projects in several parts of Kigezi especially Greater Kabale. The researcher aimed at finding the types of PMIS, quality of PMIS information output and the use of PMIS (Utilization) in resulting to project success. The researcher purposely sampled all 102 respondents, whereby 90 staff were given questionnaires and 12 Board members took part in guided interview; other forms of data collection like direct observation and face to face interview were also used. The responses of the participants were analyzed using the statistical package for social sciences (SPSS). It was found that ICOBI has different types of PMIS-PMIS and was fairly good. The information generated by the PMIS was of good quality too, PMIS users (Field staff & Administrators) have well been trained on the use of the PMIS and are very confident on the use of the system that’s finally PMIS has been of great success factor towards project success. The study further revealed that PMIS has been a tool which has enhanced positively on the success of projects. This study recommends that organization should adopt the use of PMIS in the management of their projects. PMIS guarantees better management of project because it generates quality information needed for the management of the project; this study also recommends that the environment for smooth running of the system should highly be prioritized.